Young learners' use of ICT facilities and the development of their language skills - Mat Daud, Nuraihan (IIUM Press, 2012)
This paper discusses the ICT facilities that can be used by young learners to develop their language proficiency. A longitudinal study on a child shows that PowerPoint alone provided an interesting tool to develop various aspects of writing. The older children preferred sites which were more interactive. The real audience made these sites a suitable medium for developing their communication skills. The study shows that there is an improvement in their language skills with time. The Internet was found to be a suitable tool for developing their communication skills. The analysis also shows thatthe relationship between having a computer at home and access to the Internet, and students’ performance in the English language at school was statistically significant.